ANALISIS MATERI BAHAN AJAR SEJARAH KEBUDAYAAN ISLAM MTS KELAS IX - Sofyan Habibi Anhar; Muhammad Miftah; Mohammad Khoirur Rozaq; Ilma Novi Riyanti (Fakultas Tarbiyah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
This study aims to evaluate the content or substance of Islamic Cultural History teaching materials published by the Ministry of Religion of the Republic of Indonesia at the Madrasah Tsanawiyah level for class IX semester I in the 2013 Curriculum with the domains of cognitive, affective, psychomotor, and student psychological development. This study used descriptive analysis. The results of this study found that the Islamic Cultural History teaching materials for MTs Class IX semester I discussed material that was relevant to the cognitive, affective, psychomotor and psychological developments of students. However, some of the information shown in this book is not complete, especially in the cognitive and affective domains so that this affects student development, especially in the cognitive and affective domains.